Koli woman selling fish in a lane - Mumbai Archive Project Team (Jio Institute, 2024)
In addition to selling fresh fish, Koli women may engage in fish processing activities such as drying, smoking, salting, or pickling fish to extend its shelf life. Koli women exhibit resilience and entrepreneurship, engaging in diverse activities within the fishing and seafood trade sector to support themselves and their families.